Наследуемость и изменчивость уровня содержания и выхода молочного жира как селекционных признаков в стадах черно-пестрого скота - Маменко, А.М.; Емец, З.В.; Антоненко, С.Ф. (Фактори експериментальної еволюції організмів, 2014)
Aims. According to some researchers, one of the main quality of the show-of-milk – fat – changed under the influence of various factors, the main of which are genetic. Methods. Laboratory of physico-chemical tests of an experimental material with use of the method of atomic-absorption spectrophotometry ААS-30 (Carl Zeiss, Jena), held – biometric processing of the received results. Results. It is established that increasing the fat content of the milk of the mother at the 1 % growth can be expected to fat content in milk daughter 0.29 %. The degree of influence of the factor «Father» on the fat content in milk amounted to 0.127, and the output of milk fat 0,196 at high statistical reliably-STI (P > 0.999). Conclusions. When increasing the fat content in the milk of the mother of 1% can be expected growth of this indicator for the daughters of 0.29 %. Correlation between exposure-house milk fat mothers and daughters reaches r = 0.28 (P > 0.999). Coefficients " you heritability of fat content in milk and milk output fat are respectively 0,56 and 0.72. The most significant of the genetic factor is the father. By this factor may describe 12.7 % of the variance of with-holding of fat in milk and 19.6 % of the variance of output of milk fat. There joint influence of the factor «father» to the other: «the father year calving» (η2 = USD 0.087 on the fat content and η2 = 0.11 per output of milk fat), «the father hundred-up» (η2 = 0.065, and η2 = 0.142 respectively).

Key words: milk of cows, genetically, the reliability of the impact, mother, father.